MODIFICATION OF TRIGGER SYSTEMS ON THIRD POWER ELECTRICAL CONTROL OF MEDANG VEDC PHASE - Haryanto Haryanto; Sunomo Sunomo (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2006)
AbstractThe fault of the pulse transformer and the TCA 785 triggering systems in themodule of Power Electronics made by VEDC Malang make it difficult tosubstitute due to the high prices and unavailability in Yogyakarta market.The purpose qf this application research is to substitute of TCA 785 with twooutputs by two pieces of NE 555 which work in the same manner, and tosubstitute ofpulse transformer for SCR and TRIAC phase control (firing) withoptocoupler MDC 302/ in module 501 for laboratorium practicum: Themodification is needed because of unavailability of the two components and theprice. For three phase control, the system need three pieces of both TCA 785 '.I'and pulse transformers. So, the substitution needs six pieces of both NE 555 '.I'and MOC302I '.1'. Using of optocouplerfor coupling offiring the SCR '/TRlAC '.I'is to avoid induction voltage from the main to the controlling part system whenthere is afault or short circuit in the main system.This experiment applied to the SCR firing of 0